Altruistic punishment does not increase with the severity of norm violations in the field - Loukas Balafoutas (Nature Portfolio, 2016)
Lab experiments have shown that people will punish violators of social norms, with the severity of punishment increasing with the degree of violation. Here, Balafoutas et al. show that, outside of the lab, larger violations are not punished more severely and are associated with a greater risk of reprisal.